Penggunaan Fuzzy Servqual Untuk Pengukuran Peningkatan Kualitas Pelayanan Pelanggan Dompet Digital - Anastasia Siwi Fatma Utami; Feri Prasetyo Prasetyo (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics, 2021)
Non-cash transactions are increasingly being used because they provide convenience and speed in conducting transactions. The development of technology on smartphones makes non-cash transactions can be easily used by anyone with the Digital Wallet service. There are many Digital Wallet service providers, namely, Go-Pay, Ovo, Dana and many more. With this service, it is necessary to measure customer satisfaction with the quality of services provided so that service providers know the features that are most needed by customers and strategies that must be implemented in order to continue to compete and have a positive impact on customers.This research was conducted using the Fuzzy Servqual method. The sample of this research is Bekasi City residents who use Digital Wallet services. Measurements were made based on five dimensions of service quality namely reliability, responsiveness, assurance, empathy, tangibles. The five dimensions of service quality indicate a negative gap between the service received and the service expected by the customer. While the Customer Satisfaction Index (CSI) produces a value that can be categorized into the "Satisfied" criteria.